1982
DOI: 10.1093/carcin/3.11.1255
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of azo dyes derived from benzidine, 3,3'-dimethylbenzidine and 3,3' -dimethoxybenzidine to potentially carcinogenic aromatic amines by intestinal bacteria

Abstract: The metabolism of a benzidine-based dye, Direct Black 38, a 3,3'-dimethylbenzidine-based dye, Direct Red 2 and a 3,3'-dimethoxybenzidine-based dye, Direct Blue 15 has been studied both in pure cultures of anaerobic bacteria and in bacterial suspensions derived from the intestinal contents of the rat. All of the pure cultures and the rat intestinal bacteria were able to reduce the azo linkages of Direct Black 38, Direct Red 2 and Direct Blue 15 with the subsequent formation of benzidine, 3,3'-dimethylbenzidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…Azo dyes are regarded as relatively persistent pollutants because they are not readily degraded under aerobic conditions [10][11][12]. Under anaerobic conditions, azo dyes can be reduced by intestinal bacteria and some environmental microorganisms to colorless amines, which may be toxic, mutagenic, and carcinogenic to human and animals [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes are regarded as relatively persistent pollutants because they are not readily degraded under aerobic conditions [10][11][12]. Under anaerobic conditions, azo dyes can be reduced by intestinal bacteria and some environmental microorganisms to colorless amines, which may be toxic, mutagenic, and carcinogenic to human and animals [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes are used in the textile, pharmaceutical, food, and cosmetics industries. Nitro-PAHs are ubiquitous environmental contaminants that have been detected in carbon black, photocopier toners, urban air particulates, diesel fuel emissions, used motor oil, barbecued foods, and tea leaves (1)(2)(3)(4). In mammalian systems, azo dyes and nitro-PAHs are reduced to aromatic amines by enzymes from intestinal bacteria and from the liver.…”
Section: Human Intestinal Bacteriamentioning
confidence: 99%
“…The activity of azoreductase produced by each bacterial isolate can be quantified by following the rate of decrease in the absorbance of azo dye, e.g., Direct Blue 15, at 615 nm with time (2). The activity of nitroreductase produced can be determined by measuring the conversion of 4-nitrobenzoic acid to 4-aminobenzoic acid.…”
Section: Human Intestinal Bacteriamentioning
confidence: 99%
“…It has been shown that commercially used dyes based on BZ and its derivatives can be metabolised in the human body, releasing free aminobiphenyls (Cerniglia et al, 1982). At the same time, BZ is a strong carcinogen that causes cancer in the bladder, the liver and mammary glands and also results in the development of carcinoma in the thyroid glands in animals (Sentchouk and Grintsevich, 2004).…”
Section: Introductionmentioning
confidence: 99%